The mathematics companion mathematical methods for physicists and engineers - Fischer-Cripps, Anthony C. (CRC Press, Taylor & Francis Group, 2015)
The book summarizes basic notions of mathematical methods for physicists and engineers in a schematic way. It is aimed both at science students and physicists who need a quick handy reference when they have to solve a specific mathematical problem